2020
DOI: 10.1590/1678-4324-2020190196
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil from Psidium cattleianum Sabine (Myrtaceae) Fresh Leaves: Chemical Characterization and in vitro Antibacterial Activity Against Endodontic Pathogens

Abstract: Endodontic infections result from oral pathogenic bacteria which reach and infect dental pulp, as well as surrounding tissues, through cracks, unrepaired caries and failed caries restorations. This study aims to determine the chemical composition of essential oil from Psidium cattleianum leaves (PC-EO) and to assess its antibacterial activity against endodontic bacteria. Antibacterial activity of PC-EO was evaluated in terms of its minimum inhibitory concentration (MIC) values by the broth microdilution method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Profile IX oil from Brazilian Atlantic Forest was characterized by skeletons of the types thujane (α-thujene 25.2%), p -menthane (1,8-cineole 16.4%), caryophyllane ( E -caryophyllene 10.2%), eremophilane (valencene, 8.0%), and acyclic monoterpene (myrcene, 5.0%) [ 43 ]. Also, the profile X oil from Brazilian Midwest was rich in the types aromadendrane/eudesmane (viridiflorol 17.9%, β-selinene 8.6% and aromadendrene 5.0%), caryophyllane ( E -caryophyllene 11.8% α-humulene 6.0%), and p -menthane (1,8-cineole 10.8%) [ 44 ].…”
Section: Volatile Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Profile IX oil from Brazilian Atlantic Forest was characterized by skeletons of the types thujane (α-thujene 25.2%), p -menthane (1,8-cineole 16.4%), caryophyllane ( E -caryophyllene 10.2%), eremophilane (valencene, 8.0%), and acyclic monoterpene (myrcene, 5.0%) [ 43 ]. Also, the profile X oil from Brazilian Midwest was rich in the types aromadendrane/eudesmane (viridiflorol 17.9%, β-selinene 8.6% and aromadendrene 5.0%), caryophyllane ( E -caryophyllene 11.8% α-humulene 6.0%), and p -menthane (1,8-cineole 10.8%) [ 44 ].…”
Section: Volatile Profilesmentioning
confidence: 99%
“…Psidium cattleyanum essential oils showed significant antibacterial activity against Porphyromonas gingivalis (MIC 20.0 µg/mL), Prevotella nigrescens (MIC 62.5 µg/mL), Fusobacterium nucleatum (MIC 12.5 µg/mL), Bacteroides fragilis (MIC 12.5 µg/mL), Actinomyces naeslundii (MIC 50 µg/mL), Aggregatibacter actinomycetemcomitans (MIC 6.2 µg/mL), Peptostreptococcus anaerobius (MIC 62.5 µg/mL [ 44 ], and Neisseria gonorrhoeae (MIC 13.0 µg/mL) [ 40 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Studies on the chemical composition of EOA demonstrated the β‐caryophyllene (28.83%) and α‐Pinene (28%) as the major constituents (Chrystal et al., 2020; Savoldi et al., 2020; Soliman et al., 2016); while the chemical profile of the EOG reported β‐caryophyllene (26.6%), β‐bisabolol (19.5%), limonene (17.8%), and caryophyllene oxide (15.5%) as the major components (da Silva de Souza et al., 2017; Hassan et al., 2020; Mendes et al., 2017; Silva et al., 2019). Qualitative and quantitative variations of compounds in the same EOs are common since it is well established that chemotaxonomical differences, physiological age, harvesting seasons, plant parts, and/or extraction methods may affect the composition of EOs (Dhifi et al., 2016; Khadhri et al., 2014; Mohammadhosseini et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the biological activities of EOs are strongly associated with their chemical composition. Although the chemical profile of EO from araçá and guava leaves has already been investigated (Bermúdez‐Vásquez et al., 2019; Chrystal et al., 2020; Hassan et al., 2020; Savoldi et al., 2020; Silva et al., 2019), additional studies are necessary since the high variability of chemical constituents can be influenced by external and internal factors of the plant. This information is of great relevance for the valorization of regional raw materials with outstanding biological potential.…”
Section: Introductionmentioning
confidence: 99%
“…The family Myrtaceae stands out (Chrystal et al, 2020;Gatto et al, 2020), found mainly in the southern region of Brazil, which demonstrates the importance of developing research with native fruits (Neri-Numa et al, 2018;Rodrigues et al, 2020), many still little explored (Moreira-Araújo et al, 2019) and with great potential for economic exploration (Lattuada et al, 2019;Neri-Numa et al, 2018). In this family, the Myrcianthes pungens (O. Berg) D. Legrand, popularly known as guabiju, it is a medium to large tree with around 20 m, present simple leaves and considered ornamental plant, its fruits are appreciated due to the pleasant sweet flavor (Assumpção et al, 2017).…”
Section: Introductionmentioning
confidence: 99%